Tradução como ferramenta de compreensão da língua portuguesa no curso de letras libras da Universidade Federal do Ceará - Pinheiro, Marcus Weydson (2017)
This study, which is embedded in the field of Translation Studies, corroborates the recognition of the Brazilian Sign Language, the so-called Libras, thanks to its inclusion in the Brazilian curricula of Higher Education institutions. The main objective of this research is to identify and point out the function of translation in Libras as a strategy for understanding and interpreting the text type scientific article in Portuguese in the subject “Psychology and Education of Deaf People”, within the framework of the subjects studied in area of the discipline Fundamentals of Education, part of the Libras Undergraduate Course curriculum (Teachers Training Program) at Federal University of Ceará (UFC). With special attention given to deaf students, this research intends to investigate if and how the translation of scientific texts in the Portuguese/Libras direction serves as an instrument to reach the levels of comprehension necessary to carry out the activities that require reading, translation and text/discourse production with the specific text type scientific article originally written in Portuguese. To reach the main objective of this work, this research was methodologically based on an action-research (VIEIRA, 2009), starting with, on the one hand, analyzes of extratextual and intratextual factors of a source text (ST) in Portuguese and the corresponding target text (TT) in Libras. These analyzes were carried out by six (6) deaf students regularly enrolled in the discipline “Psychology and Education of Deaf People” at UFC, who were previously instructed on the theoretical foundations proposed by Nord (2016) in the field of the Functionalist Approach to Translation. On the other hand, as part of the methodology, questionnaires were applied to the same 6 (six) deaf students, and also to the teacher of the subject “Psychology and Education of Deaf People”. As a theoretical support in the field of translation, in this research we make use of the fundamental principles of the Scope Theory, conceived by Reiss & Vermeer (1996), and of the Functionalist Approach to Translation, with our attention focused specifically on Nord’s works (2012; 2014; 2016). Our concern is based on one of our hypotheses: the need for preparation of teachers who teach the discipline “Psychology and Education of Deaf People” in the UFC Libras Undergraduate Course on questions related to the use of translation as a strategy for deaf students to be able to achieve better learning objectives by being confronted with scientific articles written in Portuguese. Because of the complexity of the text type scientific article (e. g. technical and/or scientific language, formal Portuguese language register, specific terms etc.), teachers need to present, to the students, translations of the texts in Libras, exhibited in DVD format. Thus, in our hypotheses we envisage that the students involved usually use Portuguese as a second language, thus lacking in-depth knowledge that could enable them to easily understand scientific articles written in that language. They also lack knowledge and experience with textual analyzes that take into account the different intratextual and extratextual factors such as those proposed by Nord (2016). We understand this need as a current challenge for the UFC Libras Undergraduate Course; we also think that, if measures are adopted leading to a practical understanding of these exercises, aided by theories from the field of Translation Studies, future deaf professionals that will graduate from the UFC Libras Undergraduate Course will have a more complete training and a better command of reading comprehension 11 in Portuguese. This will also certainly be reflected in the performance of their future role as educators, in which they should be committed to include deaf children and young people in society in general, nevertheless without neglecting the characteristics of the culture of deaf people. In general, our results indicate that the target group participating in the action-research is not familiar with a textual analysis model regarding both ST and TT, such as that provided by Nord’s Functionalist Approach to Translation (2016); this fact certainly makes it difficult for deaf students to understand the contents presented in the original Portuguese texts and the corresponding translation into Libras. Specifically, we can conclude, among other things, that the deaf students that we examined/interviewed during our action-research: a) need to become acquainted with the Brazilian Portuguese syntactic structures and vocabulary as well; b) need to be aware of the peculiarities of their natural/mother tongue as compared to Brazilian Portuguese as a second language; c) need to make more careful readings of scientific articles; d) lack deeper knowledge about typical concepts that are used in Text Linguistics; e) declare to increase their knowledge of specialized terminology in Libras through the scientific articles translated from LP to Libras; f) assume the importance of inclusive/and bilingual school for deaf people as a preparation for Higher Education; g) use different electronic media to obtain a better reading comprehension of scientific articles; h) majorly do not consider themselves capable of translating scientific articles from LP to Libras; i) recognize that translation is a tool that really brings advantages to reading comprehension.